COVID-19 outbreaks associated with youth club sports: Maricopa County, Arizona, September-November 2020 - Dale, A. P.; Scott, S. E.; Sunenshine, R. (American Journal of Public Health, 2022)
The Maricopa County Department of Public Health in Arizona investigated three COVID-19 outbreaks associated with club sports, two in tournaments and one in a hockey league. During September through November 2020, 195 team-associated and 69 secondary household contact cases were identified among 2093 athletes, coaches, and staff members; the team attack rate ranged from 6% to 72%. Outbreaks occurred during high community transmission periods in Maricopa County. Identification of contacts and characterization of prevention strategies were challenging because of limited cooperation from athletes, families, and staff.